THE INTERPERSONAL MEANING USED IN THE ELECTRONICS AND MOBILE PHONES IN ADVERTISEMENTS AS THE CONTRIBUTION IN TEACHING SYSTEMIC FUNCTIONAL GRAMMAR - Dias Andris Susanto (ETERNAL (English Teaching Journal), 2016)
This study aims at describing the interpersonal meaning used in the advertisements in the electronics and mobile phones. The objectives of this research are To  investigate how clauses and their constituents are structured in the English sentences used in the electronics and mobile phones advertisements, To map out how the interpersonal meanings are realized in the electronics, To  map out what are the most dominant and less dominant mood are realized in the electronics and mobile phones advertisements.The writer used a qualitative descriptive analysis to find out the interpersonal meanings used in the electronics and mobile phones advertisements. The object of the study was the sentences used. The unit analysis was a clause used in that products. The data were collected by the use of document. To analyze the data, Method of data analysis, the writer took some steps; there were identification of 5 products of the electronics and mobile phones advertisements, identification of the products, identification of the sentences used in the products, identification of the interpersonal meanings.The result shows that, the 5 products have 35 clauses and each clause has different constituents there are two, three, four, five, six, seven, eight, nine, ten, and eleven constituents. The dominant constituent is three constituents. Based on the results analysis of the interpersonal meaning in the Electronics and Mobile Phones Advertisements, we know that those five electronics and mobile phone advertisements have mood and residue. It is realized in the wordings of those clauses if we analyze it based on the interpersonal meaning elements;  Mood consists of Subject and Finite, Residue consists of Predicator, Complement, and Adjunct. From the analysis of the Mood Types above, we can see that the most dominant mood in the electronics and mobile phones advertisements is Declarative Mood and the less dominant in the electronics and mobile phones advertisements are Interrogative and Imperative Mood. It indicates that the writer of those advertisements wants to declare something or give information to the readers.It is suggested that In teaching Systemic Functional Grammar (SFG), the lectures should choose an interesting media, such as electronics and mobile phones advertisements to make the students more interesting to study and easier to understand the materials.